Gender inequality in the lives of nursing professionals during the COVID-19 Pandemic - Maria Fernanda Terra; Beatriz Hermenegildo Moglia; Gabriela Teixeira Bontempo; Sergio Kucera; Thais Izabel Ugeda Rocha (Universidade de Pernambuco, 2022)
Objective: To investigate gender-related changes in the lives of nursing professionals in 2020. Method: Qualitative research. Total sample of 106 female nursing professionals from all over the country who answered the online questionnaire, via Google Forms, with a semi-structured script. Data analysis was based on the Content Analysis proposed by Bardin. Resolution 466/12 was followed. The research was approved by the Ethics Committee. Results: The professionals pointed out gender inequalities that generated overload in their life and work routines. They cited mental suffering resulting from isolation from family members, fear of contaminating them, and suffering aggression for being seen as potential transmitters of the disease. Final Considerations: There are weaknesses resulting from the lack of state action and related to the challenges that gender adds to the struggle of nursing professionals.